Foundational Grounding and Creaturely Freedom. Issue 524 (15th October 2021) - Pearce, Kenneth L
Abstract: According to classical theism, the universe depends on God in a way that goes beyond mere (efficient) causation. I have previously argued that this 'deep dependence' of the universe on God is best understood as a type of grounding. In a recent paper in this journal, Aaron Segal argues that this doctrine of deep dependence causes problems for creaturely free will: if our choices are grounded in facts about God, and we have no control over these facts, then we do not control our choices and are therefore not free. This amounts to a grounding analogue of the Consequence Argument for the incompatibility of free will and determinism. If successful, it would have application beyond classical theism: similar concerns would apply to any view that takes our choices to be grounded in a deeper reality which is beyond our control. However, I show that the argument is not successful. Segal's Grounding Consequence Argument is so closely analogous to the Causal Consequence Argument that any response to the one provides a response to the other. As a result, if you don't think that prior causes (whether deterministic or indeterministic) undermine free will, you shouldn't think that prior grounds undermine free will.